THE EFFECTIVENESS OF ETHNOMATHEMATICAL APPROACHES ON STUDENTS' MATHEMATICAL CREATIVE THINKING SKILLS IN INDONESIA: A META-ANALYSIS STUDY - Arif Sapta Mandala; Irma Rachmah Hidayah; Dian Rahmawati (EDU-MAT: Jurnal Pendidikan Matematika, 2024)
This meta-analysis study aimed to investigate the effectiveness of ethnomathematical approaches to students' mathematical creative thinking (MCT) skills in Indonesia. Twenty-two articles in the last decade were synthesised from online databases through a rigorous selection process based on inclusion and exclusion criteria. Data analysis was carried out using a meta-analysis technique of a random effect size model using Cohen's g. This study showed that mathematics learning with an ethnomathematical approach significantly improved students' mathematical creative thinking skills with an effect size of 1.247, which is relatively large. This study does not have publication bias constraints, so the results are scientifically reliable. Therefore, this study suggests that schools in Indonesia integrate an ethnomathematical approach to mathematics learning to support students' MCT skills. Further research is recommended to develop a learning model with an ethnomathematical approach focusing on enhancing students' MCT skills.   Keywords: Meta-analysis, effectiveness, ethnomathematics, mathematical creative thinking